Development of Learning Media Using the Sparkol Videoscribe Application on Measuring Tools at Vocational High School - Sigit Purnomo; Slamet Priyanto; Eko Ady Prasetyo; Dwi Susanto (Universitas Sultan Ageng Tirtayasa, 2022)
This Study aims to (1) produce text video learning media that contains understanding, how to use, how to read measuring results, maintenance and repair of each measuring tool; (2) knowing eligibility the text video learning media using the sparkol videoscribe application;(3) knowing the student respond the text video learning media using the sparkol videoscribe application. This research includes research and development (R&D). The development modelin this study refers to the Borg and Gall model and is simplified by the puslitjaknov team into 5 steps with stages 1) Product Analysis; 2) Early Product Development; 3) Expert Validation And Revision; 4) Small Group Trials; 5) Large Group Trial And Product End. The development of learning media is declared possible to be used for learning with the results of the average score of media experts of 3.13 and materi experts of 3.33. Student Responses based on the average score of the small group trials result of 3.29 and the average score of the large group trials results of 3.32. Based on these assessments and response, the media developed is suitable use for learning.